Case Report: Cytologic Description of Somatotroph Pituitary Adenoma in a Cat - Alonso, Flavio H.; Niedringhaus, Kevin D.; Ceregatti, Mariah G.; Maglaty, Marisa A. (Frontiers in Veterinary Science, 2022)
This case report describes for the first time the cytologic characteristics of a pituitary adenoma in a cat. An eight-year-old female spayed domestic long-haired cat was referred with a previous diagnosis of hypersomatotropism and secondary diabetes mellitus 7 months before. Clinical signs included weight loss, polyphagia, polyuria and polydipsia. Serum insulin-like growth-factor was 340 nmol/L (RI: 12-92) and a presumptive diagnosis of acromegaly was made. A transsphenoidal hypophysectomy was performed. A fragment of the pituitary gland was subjected to a squash preparation and cytology revealed a neuroendocrine neoplasm associated with malignancy criteria, including anisokaryosis and prominent nucleoli. Additional cytologic findings included cell cohesiveness, indistinct cytoplasmic borders, nuclear crowding, molding and fragmentation. The histopathology analysis, however, ruled out invasion, and a diagnosis of adenoma was confirmed. A week later, during post-surgical hospitalization, the patient destabilized and died. A necropsy examination revealed fibrinosuppurative meningitis as a post-surgical complication. Pituitary adenomas might have an aggressive cytologic appearance, despite lack of histopathologic invasion.